Moving toward universal health coverage with a national health insurance program: A scoping review and narrative synthesis of experiences in eleven low- and lower-middle income countries. - Marine Flourence; Eva Jarawan; Mara Boiangiu; Fatima El Kadiri El Yamani (PLOS Global Public Health)
Universal Health Coverage (UHC) aims to provide access to quality health services to all while avoiding financial hardship. Strategies can include establishing a national health insurance scheme (NHIS). However, variations in the progress exist among countries with an NHIS. This study assesses strategies adopted in low- and lower-middle-income countries (LLMICs) with an NHIS to expand UHC. The research entailed a descriptive, qualitative review of the literature on LLMICs that have implemented an NHIS. PRISMA guidelines were used to identify studies and reports. A total of 569 texts were identified from 4 databases. A total of 78 texts were included, spanning 7 countries from Sub-Saharan Africa and 4 from Asia. The search was conducted in March 2023 and updated in April 2024. An analytical framework was used to systematically collect, analyze, and synthesize key features to review healthcare financing mechanisms and coverage dimensions. Countries generate revenue through various public and private means, including taxes, premiums, and out-of-pocket payments. Some have consolidated revenue streams into a single pool for efficiency, while others maintain separate pools. Healthcare services are procured from public and private providers, differing by country. Fee-for-service is the prevalent payment method, but capitation systems have been attempted to control expenses. Population coverage depends on whether enrollment in an NHIS is mandatory or voluntary and on its enforcement. Service provision can be comprehensive and universal or can vary with specific schemes. Mechanisms to avoid financial hardship can involve premium exemptions or subsidies. Progressing toward UHC requires addressing issues of financial sustainability, cost-containment, enrollment expansion, financial protection, and health equity. While policy options are context-specific, this review showcased experiences for other LLMICs committed to UHC with an NHIS. Recommendations on health financing include increasing the allocation of tax revenues to the insurance scheme, merging risk pools, and adopting strategic purchasing.